Morning surge, pulse wave velocity, and autonomic function tests in elderly adults - Sanchez Gelos, Diego Fernando (2012)
OBJECTIVE: To assess the complex interplay between morning surge (MS), the autonomic reflex response at the cardiovascular level, and target organ damage (arterial stiffening, left ventricle hypertrophy). METHODS: Fifty-nine consecutive elder patients (>65 years old) underwent a 24-h ambulatory blood pressure monitoring. Pulse wave velocity (PWV) was measured as an indicator of arterial stiffness. Autonomic status was assessed by scoring five conventional tests [handgrip, orthostatic pressor response, Valsalva maneuver, heart rate variation during deep breathing ('I:E'), and immediate heart rate response to standing ('30 : 15')]. RESULTS: (a) MS was correlated to left ventricle mass (P<0.005), the orthostatic pressor response (P<0.02), and blood pressure variability (BPVar) (P<0.0001) (n=59). (b) PWV explained 61.4% of MS variation for MS values 40 mmHg or less (84% of patients) (P<0.03, n=49) and 38% of MS variation in nondippers (P<0.04, n=25). (c) There were sex-related differences. PWV was associated with the orthostatic pressor response (P<0.02), 'I:E' values (P<0.04) and the '30 : 15' test (P<0.04) in men (n=14). In women (n=41), the 'I:E' values were associated with MS and BPVar (P<0.003). CONCLUSION: MS was closely related to PWV (arterial stiffening) and BPVar in a small urban sample of cardiovascular patients. MS was also associated with dysautonomia (orthostatic blood pressure/heart rate response to challenges), mostly with impaired parasympathetic modulation. MS and high BPVar cause left ventricular hypertrophy, whereas arterial stiffness alters baroreceptor sensitivity, which in turn affects BPVar, perpetuating a vicious cycle. These findings, although obtained in a small number of participants, provide relevant information not yet available in the local databases. Copyright © 2012 Wolters Kluwer Health | Lippincott Williams & Wilkins.